Cumhurbaşkanlığı Seçimlerinde Adaylık (2007 Anayasa Değişikliği ve 6271 No’lu Yasa Ekseninde Karşılaştırmalı Bir Analiz) - SEZER, ABDULLAH (My University, 2013)
Çalışmanın konusu, Türkiye’de Cumhurbaşkanlığı seçimlerinde adaylık usûlünün 2007 Anayasa değişikliği ve 6271 No.lu Yasa ekseninde ve diğer ülkelerle karşılaştırmalı analizine özgülenmiştir. Mevcut Cumhurbaşkanı (CB) A. GÜL, 28 Ağustos 2007’de TBMM’ce 3. turda 339 oyla seçildi. Ancak, 2007 Anayasa değişikliği ile, CB seçimi yetkisi TBMM’den alınarak, doğrudan halk tarafından 5 yıl için seçilmesi ve 2. kez seçilebilme olanağını da içeren yeni bir yöntem kabul edildi. 2007 Anayasa değişikliği, halkoylamasında % 68.95’lik oyla onaylandı. (Değişiklik sonrası biçimiyle) 1982 Anayasası md. 101 ve 6271 no.lu Yasa md. 7’ye göre, en az 20 TBMM üyesi veya son seçimlerde toplam oy oranı % 10’u aşan siyasal partiler, CB adayı gösterebilirler. Söz konusu % 10 baraj, Milletvekili Seçimi Kanunu’nda yer alan ve TBMM’ye giriş için öngörülen aynı oranlı ulusal seçim barajından farklıdır. (Bu baraj, Avrupa ülkeleri içinde uygulanan en yüksek baraj olup, anti-demokratik, ölçüsüz ve adaletsizdir). Yanı sıra, gerek siyasal partiler ve gerekse 20 milletvekili de, CB seçimi sürecinde aday gösterebilirler. CB seçimlerinde oy kullanma yetkisi ile donatılan halka, belli sayıda imza toplamak suretiyle CB adayı gösterebilme hakkı tanınmamıştır. Oysa devlet başkanının halk tarafından seçildiği diğer bazı ülkelerin anayasalarında, bu yönde halk inisiyatifi tanınmaktadır. Örneğin, Finlandiya (md. 54/3), Polonya (md. 124/1), Slovakya (md. 101/3), İzlanda (md. 5), hatta Doğu Timor (md. 75/1-4), vb. Bu eksiklik, Anayasa Hu- kuku ve Özgürlükler Hukuku disiplinleri ışığında incelenebilir. Çalışmanın ana bölümleri, aşağıdadır: § I. Giriş § II. Ön saptamalar § III. Osmanlı-Türkiye anayasalarında devlet başkanının belirlenme yöntemleri § IV. 2007 Anayasa değişikliği ve Cumhurbaşkanı Seçimi Kanunu § V. CB adaylık sürecine yönelik başlıca tartışmalar § VI. Sonuçlar & öneriler

In this work, the candidacy of the President of the Republic is explored through comparison with constitutions of other countries. The subject is analyzed in the light of articles 101 and 102 of the 2007 Constitutional Amendment of the Constitution of the Republic of Turkey 1982 and article 7 of Presidential Election Act dated 19 January 2012. The current President (Abdullah GÜL) was elected by the Grand National Assembly of Turkey (GNAT) on 28 August 2007 on the third ballot with vote 339. But, according to 2007 Amendment, the next President of the Republic will be elected for a five-year term by popular vote (and will be eligible for a second term). In October 2007, voters approved a referendum package of constitutional amendments including a provision for direct presidential elections with 68.95 %. According to the Constitution (art. 101) and the Act (art. 7), candidates for Presidency are to be nominated by no fewer than 20 members of GNAT, political parties which have surpass the 10 % electoral threshold in last elections or coalitions of parties which surpass this threshold in total. This threshold differs from the national electoral threshold in the Parliamentary Elections Act (the electoral threshold in Turkey for access to the GNAT is 10%) and it is antidemocratic, disproportional and unfair, and too high in comparison to other European countries. But, there is no popular initiative in this process, contrary to the other constitutions such as Finland (art. 54/3), Poland (art. 127/3), Portugal (art. 124/1), Slovakia (art. 101/3), Iceland (art. 5), and even Timor-Leste (art. 75/1-4), etc. This deficiency will be examined under the general principles of the Constitutional Law and Freedoms Law. Examined sections in this work, below mentioned: § I. Introduction § II. Preliminary determinations § III. The method of determining the head of state in OttomanTurkey constitutions § IV. The Constitutional Amendment of 2007 and the Presidential Election Act § V. The main arguments for the nomination process of the President of the Republic § VI. Conclusions & proposals
The candidacy in presidential elections in turkey [a comparative analysis in the light of the 2007 Amendment and the act]
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Social Sciences and Humanities; Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Social Sciences & Humanities; Devlet Başkanı; Cumhurbaşkanı; monarşi; adaylık; Cumhurbaşkanı adayları; Cumhurbaşkanı Seçimi Kanunu; 2007 Anayasa Değişikliği; seçim; plebisit; referandum.; Head of State; President of Republic; monarchy; candidacy; presidential candidates; Presidential Election Act; 2007 Constitutional Amendment; election; plebiscite; referendum.